Kualitas Produk dan Store Atmosphere Terhadap Keputusan Pembelian dengan Mediasi Kepercayaan Konsumen pada Naashop di Denpasar - I Gusti Ayu Agung Prajas Anggraini; I Gusti Ngurah Oka Ariwangsa; Ni Nyoman Sri Wisudawati; Putu Ayu Titha Paramita Pika (Ikatan Da'i Indonesia, 2025)
This study aims to analyze the influence of product quality and store atmosphere on purchasing decisions with consumer trust as the mediator at Naashop Denpasar. The research method used is a quantitative approach with PLS-SEM analysis of 170 respondents. The results of the study indicate that product quality has a positive and significant effect on consumer trust and purchasing decisions. Store atmosphere also has a positive and significant effect on consumer trust and purchasing decisions, although the effect is not as large as product quality. Consumer trust is proven to have a positive and significant effect on purchasing decisions. In addition, consumer trust significantly mediates the relationship between product quality and purchasing decisions, but does not mediate the relationship between store atmosphere and purchasing decisions. These results confirm that product quality is the main factor that builds trust and increases purchasing decisions at Naashop Denpasar.